Double-layer drug-loaded composite fiber membrane based on electrostatic spinning technology, and preparation method and application of double-layer drug-loaded composite fiber membrane

Through the double-layer drug-loading composite fiber membrane prepared by electrospinning technology in wound dressing, the shortcomings of existing dressings in drug loading and release control are solved, efficient and controllable drug delivery is achieved, and wounds are promoted. Healing and reducing the risk of infection.

CN119488628APending Publication Date: 2025-02-21YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411635317.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing wound dressings have shortcomings in drug loading and release control, making it difficult to achieve efficient and safe drug delivery, and cannot effectively promote wound healing and reduce the risk of infection.

Method used

The double-layer drug-loading composite fiber membrane based on electrospinning technology is adopted to improve the drug loading and release control ability through reasonable material selection and structural design. The fiber membrane consists of a hydrophobic layer and a hydrophilic layer, which uses polylactic acid and curcumin, and the hydrophilic layer uses gelatin and polyvinyl alcohol, and is prepared by electrospinning technology.

Benefits of technology

It significantly improves the drug loading and release control effect, achieves long-term drug delayed release, promotes wound healing, reduces the risk of infection, and has an efficient and controllable drug delivery system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488628A_ABST
    Figure CN119488628A_ABST
Patent Text Reader

Abstract

The invention relates to a double-layer drug-loaded composite fiber membrane based on an electrostatic spinning technology and a preparation method and application thereof in the field of auxiliary materials for transfer, and during preparation of the composite fiber membrane, a hydrophilic layer spinning solution and a hydrophobic layer spinning solution are firstly prepared, then a hydrophobic layer fiber membrane is prepared through an electrostatic spinning method, then a hydrophilic layer fiber membrane is prepared on the hydrophobic layer fiber membrane, and the hydrophilic layer fiber membrane is prepared on the hydrophobic layer fiber membrane. And after standing is carried out, the solvent is completely volatilized, and then the stable double-layer drug-loaded fiber membrane is obtained. The double-layer drug-loading fiber membrane can be applied to preparation of wound dressing; and the hygroscopicity and biocompatibility of the hydrophilic layer are beneficial to adjusting the drug release rate, keeping the wound moist, promoting healing and reducing infection, so that 30% of curcumin can be stably released within 96 hours. The fibrous membrane overcomes the problems of low drug loading capacity and poor release control in the prior art, and provides an efficient and controllable drug delivery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical materials, in particular to a drug-loaded fiber membrane and a manufacturing method thereof. The drug-loaded fiber membrane is used for manufacturing wound dressings with controlled long-term drug release. Background Art

[0002] In the medical field, wound healing and care is an important research direction. Traditional wound dressings usually use simple covers to protect wounds and prevent infection. However, these dressings lack effective drug release control and are difficult to provide sufficient drug dosage when needed, thus failing to effectively promote wound healing. In addition, many existing wound dressings have significant deficiencies in drug loading and release control, making it difficult to meet the modern medical demand for efficient and safe drug delivery.

[0003] In order to improve wound healing and reduce the risk of infection, some drug-loaded dressings have been developed in recent years. These drug-loaded dressings usually use various materials to achieve controlled drug release, such as polymer matrices. However, these materials still have room for improvement in terms of drug loading and drug release time control. Some existing drug-loaded materials have limited drug loading capacity and are difficult to achieve high drug loading; at the same time, there is instability in drug release and it is impossible to provide long-term drug release effects.

[0004] As a technology for preparing nanofibers, electrospinning has attracted widespread attention because it can prepare ultrafine fibers and fiber membranes with a large specific surface area. Electrospinning technology can achieve uniform distribution and effective loading of drugs, thereby increasing drug loading. In addition, by adjusting the spinning parameters and material combination, controlled release of drugs can be achieved to meet different treatment needs.

[0005] At present, some double-layer drug-loaded fiber membranes have been proposed, which regulate the release of drugs through different material combinations. However, most existing double-layer fiber membranes are still not ideal in terms of drug loading and release control. Therefore, developing a double-layer drug-loaded fiber membrane with high drug loading and long-term controlled release is of great significance to improve the effect of wound care.

[0006] Based on the above background, the present invention provides a new double-layer drug-loaded fiber membrane based on electrospinning technology. Through reasonable material selection and structural design, the drug loading capacity and release control performance are significantly improved, providing a highly efficient and controllable drug delivery system for wound dressings. Summary of the invention

[0007] The purpose of the present invention is to provide a double-layer drug-loaded composite fiber membrane based on electrospinning technology, a preparation method and use thereof. The prepared drug-loaded composite fiber membrane is particularly suitable for the field of wound dressings. Through reasonable material selection and structural design, the double-layer fiber membrane of the present invention can increase the drug loading amount and controlled release effect, thereby significantly improving the wound healing effect and reducing the risk of infection.

[0008] The technical solution for achieving the purpose of the present invention is as follows:

[0009] A method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology comprises the following steps:

[0010] (1) Preparation of hydrophilic layer spinning solution

[0011] Dissolve polyvinyl alcohol with a degree of alcoholysis of 87-89% in deionized water to form a polyvinyl alcohol solution with a concentration of 0.5-1.5 g / 10 mL, heat the solution to 70-90° C. and stir until it is completely dissolved; then dissolve gelatin in deionized water to form a gelatin solution with a concentration of 0.3-0.8 g / 10 mL, heat the solution to 40-60° C. and stir until it is completely dissolved;

[0012] The polyvinyl alcohol solution and the gelatin solution are mixed in a volume ratio of 7:3, and stirred at room temperature to 50° C. for 5 to 15 minutes to obtain a hydrophilic layer spinning solution;

[0013] (2) Preparation of hydrophobic layer spinning solution

[0014] Dissolve polylactic acid in dichloromethane, heat to 70-80°C, and stir until completely dissolved to form a polylactic acid-dichloromethane solution with a polylactic acid concentration of 0.8-1.2 g / 10 mL; add curcumin to the above solution, stir until the curcumin is completely dissolved, and obtain a hydrophobic layer spinning solution;

[0015] (3) Preparation of hydrophobic layer fiber membrane

[0016] The hydrophobic layer spinning solution is sucked into the needle tube, and the electrospinning needle is used to perform electrospinning under the condition of a voltage difference of 15 kV, a flow rate of 1 mm / min, a receiving distance of 15 cm, and a silicone oil paper laid on a flat plate is used as a base material to form a hydrophobic layer fiber membrane on the silicone oil paper;

[0017] (4) Preparation of hydrophilic layer fiber membrane on hydrophobic layer fiber membrane

[0018] The prepared hydrophilic layer spinning solution is sucked into the needle tube to ensure that the liquid is uniform and free of bubbles, and then the needle tube is installed on the electrospinning device, and the spinning parameters are set to a voltage difference condition of 12kV, a spinning flow rate of 0.1 mm / min, and a receiving distance of 15 cm; after the spinning device is prepared, the hydrophobic layer fiber membrane with silicone oil paper that has been prepared before is taken and placed on the receiver as a substrate; the electrospinning equipment is started, and the spinning solution is sprayed out at a set flow rate under the action of the voltage difference, and the fibers are gradually deposited on the hydrophobic layer fiber membrane, forming a three-layer composite structure with a hydrophilic layer fiber membrane on the upper layer, a hydrophobic layer fiber membrane in the middle, and a silicone oil paper on the bottom layer;

[0019] (5) Obtaining a double-layer drug-loaded fiber membrane

[0020] After spinning, the fiber membrane with the hydrophilic layer on the upper layer and the hydrophobic layer in the middle layer is peeled off from the silicone oil paper as a whole, and after standing to allow the solvent to completely evaporate, a stable double-layer drug-loaded fiber membrane is obtained.

[0021] In step (1), the alcoholysis degree of the polyvinyl alcohol is preferably 88%.

[0022] In step (2), the ratio of the amount of curcumin added to the amount of dichloromethane in the hydrophobic layer spinning solution is 0.1 to 0.3 g / 10 mL. Curcumin and polylactic acid form a uniformly distributed mixture.

[0023] In step (2), the concentration of polylactic acid in the polylactic acid-dichloromethane solution is preferably 1.0 g / 10 mL.

[0024] In steps (3) and (4), the ambient temperature is controlled at 25° C. and the humidity is controlled at 50% during the electrospinning process.

[0025] In step (4), the flow rate of the hydrophilic layer spinning solution is 0.1 mm / min.

[0026] A double-layer drug-loaded composite fiber membrane based on electrospinning technology is prepared based on the above preparation method and is used to make wound dressings.

[0027] Compared with the prior art, the present invention has the following advantages: the double-layer fiber membrane of the present invention uses polylactic acid and gelatin-polyvinyl alcohol as the base material, combined with electrospinning technology, which significantly improves the drug loading and release control ability of the drug. Through the reasonable design of the hydrophobic layer and the hydrophilic layer, the efficient loading and long-term sustained release effect of the drug are achieved. The fiber membrane can promote wound healing, reduce the risk of infection, and improve the treatment effect in the application of wound dressings, and has broad application prospects and market value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Scanning electron microscope images of the hydrophobic membrane (a) and the hydrophilic membrane (b) surfaces.

[0029] Figure 2 Diameter distribution diagram of hydrophobic membrane (a) and hydrophilic membrane (b).

[0030] Figure 3 This is the infrared spectrum of the hydrophobic membrane.

[0031] Figure 4 This is the infrared spectrum of the hydrophilic membrane.

[0032] Figure 5 (a) UV-visible absorption spectrum of curcumin and (b) standard curve of curcumin concentration.

[0033] Figure 6 This is the release kinetics curve of curcumin. DETAILED DESCRIPTION

[0034] The present invention further describes the preparation method and application of the double-layer drug-loaded fiber membrane based on electrospinning technology through the following specific embodiments.

[0035] Example 1

[0036] A method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology is carried out in the following steps: 1. Preparation of hydrophilic layer spinning solution

[0037] (1) Preparation of polyvinyl alcohol solution:

[0038] Take 1 gram of polyvinyl alcohol (PVA) and add it to 10 milliliters of deionized water.

[0039] The mixture was stirred at 80° C. and 300 rpm for 30 minutes until the polyvinyl alcohol was completely dissolved, thereby obtaining a 10% polyvinyl alcohol solution.

[0040] (2) Preparation of gelatin solution:

[0041] Take 0.6 g of gelatin and add it to 10 ml of deionized water.

[0042] The mixture was stirred at 300 rpm at 50°C for 10 minutes until the gelatin was completely dissolved to obtain a 6% gelatin solution.

[0043] (3) Preparation of hydrophilic layer spinning solution:

[0044] Mix 7 ml of the polyvinyl alcohol solution with 3 ml of the gelatin solution.

[0045] The mixture was stirred at 300 rpm for 10 minutes to obtain 10 ml of a uniform hydrophilic layer spinning solution.

[0046] 2. Preparation of hydrophobic layer spinning solution

[0047] (1) Preparation of polylactic acid solution:

[0048] Take 1 gram of polylactic acid (PLA) and add it to 10 milliliters of dichloromethane (DCM). The amount of polylactic acid used can be 0.8 to 1.2 g.

[0049] The mixture was stirred at 300 rpm at 50° C. for 1 hour until the polylactic acid was completely dissolved to form a clear polylactic acid solution.

[0050] (2) Addition of curcumin:

[0051] Add 0.3 g of curcumin to the polylactic acid solution. The amount of curcumin used can be 0.1 to 0.3 g.

[0052] The mixture was stirred at 300 revolutions per minute at a temperature of 40° C. for 5 minutes until the curcumin was completely dissolved to obtain a hydrophobic layer spinning solution.

[0053] 3. Preparation of hydrophobic layer fiber membrane

[0054] The hydrophobic layer spinning solution was aspirated into a 10 ml syringe and a 20 G electrospinning needle was used.

[0055] Set the electrospinning equipment to a negative electrode voltage of -3 kV and a positive electrode voltage of +12 kV, a flow rate of 1 mm / min, and a receiving distance of 15 cm.

[0056] At room temperature (about 25°C) and 50% relative humidity, a hydrophobic layer fiber membrane was prepared by electrospinning, using a flat plate covered with silicone oil paper as a collecting device and the silicone oil paper laid on the flat plate as a base material to form a hydrophobic layer fiber membrane on the silicone oil paper.

[0057] 4. Preparation of hydrophilic layer fiber membrane on hydrophobic layer fiber membrane

[0058] The hydrophilic layer spinning solution was aspirated into a 10 ml syringe and the same 20G electrospinning needle was used.

[0059] Set the negative electrode voltage to -3kv and the positive electrode voltage to +9kv, the flow rate to 0.1mm / min, and the receiving distance to 15cm.

[0060] Under the same room temperature and humidity conditions, after preparing the spinning device, take the previously prepared hydrophobic layer fiber membrane with silicone oil paper and place it on the receiver as a substrate; start the electrospinning equipment, and the spinning liquid is sprayed out at a set flow rate under the action of voltage difference, and the fibers are gradually deposited on the hydrophobic layer fiber membrane, forming a three-layer composite structure with a hydrophilic layer fiber membrane on the upper layer, a hydrophobic layer fiber membrane in the middle layer, and silicone oil paper on the bottom layer.

[0061] 5. Obtaining double-layer drug-loaded fiber membrane

[0062] After spinning is completed, the hydrophilic layer fiber membrane and the hydrophobic layer fiber membrane are carefully peeled off from the silicone oil paper.

[0063] The mixture was then placed at room temperature for 30 minutes to ensure that the solvent was completely evaporated, and finally a structurally stable double-layer drug-loaded fiber membrane was obtained.

[0064] The above double-layer drug-loaded fiber membrane was tested, and the test results are as follows Figure 1-Figure 5 shown.

[0065] Figure 1 : (a) is the scanning electron microscope (SEM) image of curcumin-polylactic acid (PLA) fiber membrane, which clearly shows that the curcumin nanoparticles are evenly distributed and wrapped by PLA fibers; (b) is the scanning electron microscope (SEM) image of gelatin-polyvinyl alcohol (PVA) fiber membrane, which shows the uniform and continuous fiber structure formed by the co-spinning of gelatin and polyvinyl alcohol.

[0066] Figure 2 : (a) is the diameter distribution diagram of polylactic acid-curcumin electrospun fibers, with an average fiber diameter of about 5136nm; (b) is the diameter distribution diagram of gelatin-polyvinyl alcohol electrospun fibers, with an average fiber diameter of 369nm.

[0067] Figure 3 The infrared spectra of curcumin, polylactic acid and curcumin-polylactic acid electrospun fiber membrane are shown. In the curcumin-polylactic acid electrospun fiber membrane, characteristic absorption peaks of curcumin (such as 1600-1700 -1 The characteristic absorption peaks of aromatic ring C=C stretching vibration and polylactic acid (such as 1750cm -1 This indicates that curcumin was successfully introduced into the polylactic acid fiber and maintained the integrity of its molecular structure.

[0068] Figure 4 The infrared spectra of gelatin, polyvinyl alcohol and gelatin-polyvinyl alcohol electrospun fibers are shown. In gelatin-polyvinyl alcohol electrospun fibers, characteristic absorption peaks of gelatin (such as 3300cm -1 NH stretching vibration) and characteristic absorption peaks of polyvinyl alcohol (such as 2900cm -1 These results indicate that the main molecular features of PVA and gelatin are retained during the electrospinning process, thus endowing the final fiber material with excellent mechanical properties and biocompatibility.

[0069] Figure 5The UV-visible absorption spectrum of curcumin (a) and its concentration standard curve (b) are shown. In (a), curcumin shows a clear absorption peak at about 204 nm, which is consistent with the characteristic absorption wavelength of curcumin. (b) shows the standard curve between curcumin concentration and absorbance, with a high degree of fit (R 2 =0.997), indicating that the detection method has good linear relationship and reliability.

[0070] Example 2

[0071] The double-layer drug-loaded fiber membrane was used to make wound dressings, and the following tests were further performed:

[0072] (1) Cut the prepared double-layer drug-loaded fiber membrane into pieces of appropriate size and apply them to the wound site.

[0073] (2) The fiber membrane can gradually release curcumin, releasing 20% ​​of the drug within 96 hours, thereby providing sustained antibacterial and anti-inflammatory effects.

[0074] (3) Through the design of the double-layer structure, the polylactic acid in the hydrophobic layer provides drug loading and initial release functions, while the gelatin and polyvinyl alcohol in the hydrophilic layer achieve the sustained release effect of the drug, which is suitable for wound care that requires long-term drug release control.

[0075] Figure 6 The release kinetics curve of curcumin was displayed, and the results showed that in the initial 2-24 hours, the release rate of curcumin was relatively fast, and the release amount reached about 22%. Within 96 hours, the cumulative release of curcumin was about 30%. These results show that the release of curcumin in the double-layer fiber membrane has the characteristics of initial rapid release and subsequent sustained release, which is conducive to long-term maintenance of drug efficacy.

[0076] The double-layer drug-loaded fiber membrane of the present invention has a simple preparation process and reasonable material selection, can significantly improve the drug loading amount and release control effect, and has high application value and market prospects.

[0077] On the basis of Example 1, relevant parameters were changed to verify the rationality of the value range, and the results are shown in Tables 1-3 below.

[0078] Table 1 shows the viscosity and spinnability of different proportions of polyvinyl alcohol gelatin

[0079]

[0080] Table 1 shows the viscosity and electrospinnability data of polyvinyl alcohol gelatin at different ratios. As can be seen from the table, as the ratio of polyvinyl alcohol to gelatin increases, the viscosity gradually increases. It is particularly noteworthy that the ratio of 7:3 has a viscosity of 343.2mPa·s, showing good electrospinnability, indicating that this ratio has better rheological properties during the electrospinning process and is suitable for fiber preparation. This ratio is superior to other ratios in terms of spinnability and is an effective choice for fiber preparation.

[0081] Table 2 shows the diameter distribution of hydrophilic layer fibers under different voltage differences.

[0082] Voltage(kV) Diameter(nm) Spinnability 9 —— Not spinnable 12 369±156 Spinnable 15 346±203 Low spinnability 18 301±161 Low spinnability

[0083] Table 2 shows the diameter distribution of the hydrophilic layer fiber at different voltages. At a voltage difference of 12 kV, the fiber diameter distribution is 369 ± 156 nm, indicating that a relatively uniform fiber diameter can be obtained at this voltage, and the spinnability is good. In contrast, spinning is not possible at 9 kV, and the fiber diameter is smaller but more widely distributed at voltage differences of 15 kV and 18 kV, showing poor spinnability. Therefore, a voltage difference of 12 kV is the preferred voltage for achieving better spinning effects.

[0084] Table 3 shows the diameter distribution of hydrophobic layer fibers under different voltage differences.

[0085] Voltage(kV) Diameter(nm) Spinnability 9 5932±893 Not spinnable 12 5649±651 Low spinnability 15 5136±432 Spinnable 18 4617±617 Spinnable

[0086] Table 3 shows the diameter distribution of the hydrophobic layer fiber under different voltages. At a voltage difference of 15 kV, the fiber diameter is 5136 ± 432 nm, showing a small diameter fluctuation and good spinnability, indicating that relatively stable and uniform fibers can be obtained at this voltage. Compared with other voltages, a voltage difference of 15 kV provides better spinning conditions, which is conducive to the preparation of higher quality fibers. Spinning is poor at a voltage difference of 9 kV, and although spinning is possible at voltage differences of 12 kV and 18 kV, the fiber diameter distribution fluctuates greatly and the spinnability is poor.

Claims

1. A method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology, characterized in that: The following steps are involved: (1) Preparation of hydrophilic layer spinning solution Dissolve polyvinyl alcohol with a degree of alcoholysis of 87-89% in deionized water to form a polyvinyl alcohol solution with a concentration of 0.5-1.5 g / 10 mL, heat the solution to 70-90°C and stir until it is completely dissolved; then dissolve gelatin in deionized water to form a gelatin solution with a concentration of 0.3-0.8 g / 10 mL, heat the solution to 40-60°C and stir until it is completely dissolved; The polyvinyl alcohol solution and the gelatin solution are mixed in a volume ratio of 7:3, and stirred at room temperature to 50° C. for 5 to 15 minutes to obtain a hydrophilic layer spinning solution; (2) Preparation of hydrophobic layer spinning solution The polylactic acid is dissolved in dichloromethane, heated to 70-80°C, and stirred until completely dissolved to form a polylactic acid-dichloromethane solution with a polylactic acid concentration of 0.8-1.2 g / 10 mL; curcumin is added to the above solution, and stirred until the curcumin is completely dissolved to obtain a hydrophobic layer spinning solution; (3) Preparation of hydrophobic layer fiber membrane The hydrophobic layer spinning solution is sucked into the needle tube, and the electrospinning needle is used to perform electrospinning under the condition of a voltage difference of 15 kV, a flow rate of 1 mm / min, a receiving distance of 15 cm, and a silicone oil paper laid on a flat plate is used as a base material to form a hydrophobic layer fiber membrane on the silicone oil paper; (4) Preparation of hydrophilic layer fiber membrane on hydrophobic layer fiber membrane The prepared hydrophilic layer spinning solution is sucked into the needle tube to ensure that the liquid is uniform and free of bubbles. The needle tube is then installed on the electrospinning device. The spinning parameters are set to a voltage difference condition of 12 kV, a spinning flow rate of 0.1 mm / min, and a receiving distance of 15 cm. After the spinning device is prepared, the hydrophobic layer fiber membrane with silicone oil paper prepared previously is taken and placed on the receiver as a substrate. The electrospinning equipment is started, and the spinning solution is ejected at a set flow rate under the action of voltage difference, and the fibers are gradually deposited on the hydrophobic fiber membrane to form a three-layer composite structure with an upper hydrophilic fiber membrane, a middle hydrophobic fiber membrane, and a bottom silicone paper. (5) Obtaining a double-layer drug-loaded fiber membrane After spinning, the fiber membrane with the hydrophilic layer on the upper layer and the hydrophobic layer in the middle layer is peeled off from the silicone oil paper as a whole, and after standing to allow the solvent to completely evaporate, a stable double-layer drug-loaded fiber membrane is obtained.

2. The method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology according to claim 1, characterized in that: In step (1), the alcoholysis degree of polyvinyl alcohol is 88%.

3. The method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology according to claim 1, characterized in that: In step (2), the ratio of the amount of curcumin added to the amount of dichloromethane in the hydrophobic layer spinning solution is 0.1-0.3 g / 10 mL.

4. The method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology according to claim 1, characterized in that: In step (2), the concentration of polylactic acid in the polylactic acid-dichloromethane solution is 1.0 g / 10 mL.

5. The method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology according to claim 1, characterized in that: In steps (3) and (4), the ambient temperature was controlled at 25°C and the humidity was controlled at 50% during the electrospinning process.

6. The method for preparing a double-layer drug-loaded composite fiber membrane based on electrospinning technology according to claim 1, characterized in that: In step (4), the flow rate of the hydrophilic layer spinning solution is 0.1 mm / min.

7. A double-layer drug-loaded composite fiber membrane based on electrospinning technology prepared according to the preparation method according to any one of claims 1 to 6.

8. The use of a double-layer drug-loaded composite fiber membrane based on electrospinning technology according to claim 7, characterized in that: Used to make wound dressings.